2020
DOI: 10.1001/jamanetworkopen.2020.28856
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in US Heart Transplant Outcomes and Consequences for Health Care Equity

Abstract: Heart transplant outcomes in the US are generally improving but are still far from ideal. One-year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Under this concept, the distance between the donor and transplant hospital is part of a composite score, which also includes the medical acuity of the waitlisted patient and the biologic match with the donor [29 & ]. Geographic disparities affecting heart tation include heterogeneity in regional donor availability [30,31], distance traveled impacting graft ischemic time (Fig. 4) [30,32,33], and local socioeconomic disparities [30,34] including access to care.…”
Section: Geographic Disparities In Lung and Heart Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this concept, the distance between the donor and transplant hospital is part of a composite score, which also includes the medical acuity of the waitlisted patient and the biologic match with the donor [29 & ]. Geographic disparities affecting heart tation include heterogeneity in regional donor availability [30,31], distance traveled impacting graft ischemic time (Fig. 4) [30,32,33], and local socioeconomic disparities [30,34] including access to care.…”
Section: Geographic Disparities In Lung and Heart Transplantationmentioning
confidence: 99%
“…Geographic disparities affecting heart tation include heterogeneity in regional donor availability [30,31], distance traveled impacting graft ischemic time (Fig. 4) [30,32,33], and local socioeconomic disparities [30,34] including access to care. Studies have shown that the number of transplant centers vary per state [30,35] affecting both waitlist mortality and rate of transplantation even after adjusting for recipient acuity of illness [35].…”
Section: Geographic Disparities In Lung and Heart Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart transplantation (HTx) is the gold standard for the treatment of terminal heart failure that is refractory to conventional medical treatment [ 1 ]. Although the procedure is effective, chronic rejection and cardiac allograft vasculopathy (CAV) still continue to limit the long-term success of HTx (1-year and 10-year survival of 85% and 60%, respectively) [ 1 , 2 , 3 , 4 ]. Thus, novel diagnostic and prognostic tools for the long-term monitoring of HTx patients at risk of developing allograft vasculopathy are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Heart transplantation (HTx) is considered a standard therapy for patients with end-stage heart failure refractory to medical treatment. Currently, the one-year and 10-year survival is around 85% and 60%, respectively, thus calling for further improvements in short-and long-term outcomes (1). The number of patients with end-stage heart failure is increasing, while the limited number of available donor organs is still a major limiting factor to the broader applicability of HTx (2).…”
Section: Introductionmentioning
confidence: 99%